Feature Acquisition in Second Language Phonetic Development: Evidence From Phonetic Training. Issue 2 (25th January 2019) - Olson, Daniel J.
Abstract: This study employed a targeted phonetic instruction to explore the mechanisms that underpin second language (L2) phonetic acquisition. Broadly, two general approaches to phonetic acquisition have been previously proposed. A segmental approach suggests that learners acquire a series of individual, discrete phonemes (e.g., Flege, 1995), while a featural approach posits that L2 phonetic development occurs at the subsegmental level of the feature, which may be shared across multiple phonemes (e.g., de Jong, Hao, & Park, 2009). This study extended this line of research, using a visual feedback paradigm to train English speakers on one of the three voiceless stop consonants in Spanish. Analysis focused on the change in voice onset time across three testing sessions (pretest, posttest, delayed posttest). Results demonstrated a significant change in voice onset time for trained and nontrained phonemes, suggesting that featural changes generalize to related phonemes. Theoretical and pedagogical implications are discussed. Abstract :